2021
DOI: 10.1177/08901171211050369
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stress as a Pathway for the Relationship Between Neighborhood Factors and Glycemic Control in Adults With Diabetes

Abstract: Purpose Neighborhood factors such as crime, discrimination, and violence are increasingly recognized as correlates of poor glycemic control. However, pathways for these relationships are unclear. This study examined stress and self-efficacy as potential pathways for the relationship between neighborhood factors and glycemic control in adults with type 2 diabetes. Design Cross-sectional study. Setting Two primary care clinics in southeastern US. Participants 615 adults aged 18 years and older. Measures Validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…The association between neighborhood and the built environment and glycemic target achievement has been addressed in nine included studies (20%) (Campbell et al, 2021; Carpio & Stewart, 2016; Egede et al, 2022; Hu et al, 2022; Levy et al, 2022; Smalls et al, 2015; Tabaei et al, 2018; Walker et al, 2015; Zahedi-Spung et al, 2022). The results indicate that various factors in deprived neighborhoods were associated with not achieving glycemic targets.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The association between neighborhood and the built environment and glycemic target achievement has been addressed in nine included studies (20%) (Campbell et al, 2021; Carpio & Stewart, 2016; Egede et al, 2022; Hu et al, 2022; Levy et al, 2022; Smalls et al, 2015; Tabaei et al, 2018; Walker et al, 2015; Zahedi-Spung et al, 2022). The results indicate that various factors in deprived neighborhoods were associated with not achieving glycemic targets.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicate that various factors in deprived neighborhoods were associated with not achieving glycemic targets. These factors include high neighborhood problems (Hu et al, 2022), the presence of only one store or lack of stores in the neighborhood (Levy et al, 2022), neighborhood violence and social cohesion (Smalls et al, 2015), lower social support (Walker et al, 2015), deprived neighborhoods (Tabaei et al, 2018; Zahedi-Spung et al, 2022), and neighborhood crime and violence (Egede et al, 2022). However, one of the included studies found that a lower-income neighborhood and the built environment were not significantly associated with poor glycemic target achievement in adults (Campbell et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These cardio-health conditions are known to negatively impact cognition (Gorelick et al, 2017) including episodic memory (Gonzales et al, 2017), and thought to increase health disparities in cognition (De Anda-Duran et al, 2022) and motor functions (e.g., gait; Niermeyer, 2018 for a systematic review). Additionally, a recent study found that adverse neighborhood conditions are directly related to participantlevel psychosocial stress-levels of which negatively impact the Hypothalamic-Pituitary-Adrenal axis in humans (Gerritsen et al, 2010) as well as microglia-dependent mechanisms in rodents (Garvin and Bolton, 2022)-and this stress was in turn related to negative health outcomes (Egede et al, 2022). Thus, it would seem that neighborhood-level social vulnerability gets "under the skin" and "into the brain" of older adults to influence both cognitive and motor outcomes.…”
Section: Discussionmentioning
confidence: 99%